Empowerment of Lurik Woven Small and Medium Enterprises to Face the Global Market with Multi Disciplines - Edy Prayitno; Uyuunul Mauidzoh; Wahyu Eka Priana Sukmawaty; Nerys Lourensius L. Tarigan (Journal of International Conference Proceedings (JICP), 2020)
Lurik fabrics, fabrics in the form of lines, are one of Indonesia's traditional woven fabrics that must get support to survive in competition with other fashion products, both nationally and globally. The complexity of the problems faced by small and medium industries engaged in weaving requires support from various scientific fields, namely industrial engineering, fashion, management, and information technology. In general, the support provided is to increase the quality and quantity of products produced, improve management, and expand the marketing network. Each of these divisions provides direct technical support in accordance with existing concrete problems. The industrial engineering division rearranged the production space so that it is more comfortable, safe and conducive to work. The Clothing Department provides training in the manufacture of derivative products from striated fabrics, so that derivative products with high economic value will be produced to be marketed. The Management Division improves the management of financial records and marketing planning, as well as the management of Intellectual Property Rights for their lurik motives. Information technology department, created a website for wider information dissemination, and created an online shop in several existing marketplaces. Some of the results of this assistance include a neatly arranged production room, a production machine with a production capacity of 2 times as much; 6 employees master the manufacture of derivative products with 3 product variants; 5 Intellectual Property Rights for lurik motives; 1 active website; 2 online shops. Overall, these activities have increased the quality and quantity of production produced, as well as market expansion.